The Municipal Control Function in Colombia: From political and juridical to the administrative. - Tovar, Luis Freddyur (2023)
This article is a reflection on the results of research into the role of political control performed by the City Council of Santiago de Cali within the context of the City Development Plan titled “To live a life with dignity” designed for the administration of Jorge Ivan Ospina Gomez, which ran from 2008- 2011. The research was carried out in 2014. The research was based on the following hypothesis: The control performed in the municipalities in Colombia drifts from the political and legal areas to a purely administrative mode of control. To check the validity and veracity of such a claim the investigation examined various relevant theories and tested them against empirical evidence. The text is divided into three parts: first, conceptualization and theorization of political control in Colombia; second, the description of the research; and third, analysis of the results. The research is framed in terms of the political control mechanisms provided for in the 1991 Colombian Constitution.